396. Clinical Features of Proven and Probable Cases of Histoplasmosis and the Role of Urinary Histoplasma Antigen Testing: A Case Series From India. (26th November 2018) - Bansal, Nitin; Sethuraman, Nandini; R., Madhumitha; Nambi, P Senthur; D, Suresh Kumar; Ramasubramanian, V; Gopalakrishnan, Ram
Abstract: Background: Histoplasmosis is considered uncommon in India, and the diagnosis usually depends on invasive tissue sampling. The histoplasma urinary antigen assay is a non-invasive test that has been recently introduced in India. Methods: This was a single-centre retrospective study done from January 2013 till February 2018. Case records of patients with proven (confirmed by demonstrating intra-cellular yeast like organisms on histopathology or culture) and probable (presence of antigenuria—done by IMMY Alpha Histoplasma enzyme immunoassay) histoplasmosis were analysed. Results: A total of 37 patients (18 proven and 19 probable) with mean age of 51.59 ± 11.17 years were studied. Diabetes was the most common co-morbidity (15 patients) followed by HIV (6), whereas no co-morbidity was found in 10 patients. Adrenals (29%), lungs (27%), lymph nodes (27%), and skin and oral mucosa (24.3%) were the most common organs involved (Figure 1). Anti-tubercular therapy based on granulomatous inflammation was given to 10 patients prior to the diagnosis. Raised GGTP and ALP (54%) and hyperglobulinemia (40%) were the common laboratory features. Most patients (83.7%) came from endemic areas (North-Eastern states, West Bengal, and Bangladesh) whereas all six cases from non-endemic areas were classified as probable (Figure 2). All-cause mortality rate was 10.8%, with 27 cases (72.9%) showing improvement at a median follow-up of 6 months. Comparison of proven and probable cases revealed that the following features were significantly higher in theprobable group: female sex ( P = 0.001), coming from nonendemic areas ( P = 0.009), requiring in-patient care ( P = 0.001), leucocytosis ( P = 0.043), absence of skin and oral mucosal findings ( P = 0.002), simultaneous alternate diagnosis ( P = 0.039), and death ( P = 0.039). Conclusion: This study emphasises that histoplasmosis is an under recognised entity in India. Histoplasma antigenuria does help in making the diagnosis easily and needs to be more extensively utilized by clinicians. However, it can yield false-positive results in patients belonging to nonendemic areas and lacking typical clinical features of histoplasmosis. Further studies are needed to determine the utility of the antigen test in Indian settings. Disclosures: All authors: No reported disclosures.